2018
DOI: 10.3389/fmicb.2018.02383
|View full text |Cite
|
Sign up to set email alerts
|

Low 15N Natural Abundance in Shoot Tissue of Brachiaria humidicola Is an Indicator of Reduced N Losses Due to Biological Nitrification Inhibition (BNI)

Abstract: The tropical forage grass Brachiaria humidicola (Bh) suppresses the activity of soil nitrifiers through biological nitrification inhibition (BNI). As a result, nitrate (NO3−) formation and leaching are reduced which is also expected to tighten the soil nitrogen (N) cycle. However, the beneficial relationship between reduced NO3− losses and enhanced N uptake due to BNI has not been experimentally demonstrated yet. Nitrification discriminates against the 15N isotope and leads to 15N depleted NO3−, but 15N enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
(56 reference statements)
2
18
1
Order By: Relevance
“…Lower δ 15 N values indicate reduced soil microbial nitrification, a process known for strong isotopic N fractionation, which results in 15 N enrichment of source N (soil NH 4 + ) ( 39 , 40 ). Brachiaria grass genotypes that have a high BNI capacity in root systems show lower δ 15 N in leaf tissues compared to low BNI capacity genotypes ( 41 ). Lower grain δ 15 N observed in BNI-MUNAL, 16% lower ( P < 0.002) than in MUNAL control ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lower δ 15 N values indicate reduced soil microbial nitrification, a process known for strong isotopic N fractionation, which results in 15 N enrichment of source N (soil NH 4 + ) ( 39 , 40 ). Brachiaria grass genotypes that have a high BNI capacity in root systems show lower δ 15 N in leaf tissues compared to low BNI capacity genotypes ( 41 ). Lower grain δ 15 N observed in BNI-MUNAL, 16% lower ( P < 0.002) than in MUNAL control ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the corn-Urochloa intercrop, the recovery of N in fertilizer was higher than in corn monoculture (Almeida et al, 2018d) and the greater recovery in soil profiles between 0.6 and 1.0 m was probably related to Urochloa roots reaching deep layers, thus reducing N-losses by leaching. Reduced leaching might as well be attributed to the BNI promoted by Urochloa root exudation (Karwat et al, 2018). Also, Galdos et al (2020) reported that the finer roots of U. brizantha promoted a more complex pore system in the soil, reducing solute flow and reducing N leaching when compared to corn or even U. ruziziensis.…”
Section: N Cyclingmentioning
confidence: 99%
“…Indeed, Urochloa spp. have a variety of strategies, which could affect the δ 15 N signature of their biomass [31]. First, grasses of the genus Urochloa can obtain 20% to 40% of their total N in the plant from the atmosphere through the association with N fixing bacteria (i.e., non-symbiotic N 2 fixation) [32,33].…”
Section: Introductionmentioning
confidence: 99%